2022
DOI: 10.3389/fmicb.2022.907531
|View full text |Cite
|
Sign up to set email alerts
|

More than you can see: Unraveling the ecology and biodiversity of lichenized fungi associated with leaves and needles of 12 temperate tree species using high-throughput sequencing

Abstract: More than you can see: Unraveling the ecology and biodiversity of lichenized fungi associated with leaves and needles of temperate tree species using high-throughput sequencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…in the much drier, submontane forests of Brazil (1200 and 1700 mm; et al, 2021). These results indicate that epiphylls do not only depend on the presence of a superhost, such as Danaea nodosa at our study site, but also on the right environmental conditions such as high rainfall and air humidity (Tanunchai et al, 2022). Leaf longevity alone is not the only important factor for epiphyll colonization either, because three of our studied fern species with even longer leaf life spans (Lomariopsis recurvata, Mickelia bernoullii and Mickelia pergamentacea) were colonized by fewer foliicolous lichens (2-9 species after 26 months).…”
Section: Richness and Composition Of Three Groups Of Epiphylls On Fernsmentioning
confidence: 58%
“…in the much drier, submontane forests of Brazil (1200 and 1700 mm; et al, 2021). These results indicate that epiphylls do not only depend on the presence of a superhost, such as Danaea nodosa at our study site, but also on the right environmental conditions such as high rainfall and air humidity (Tanunchai et al, 2022). Leaf longevity alone is not the only important factor for epiphyll colonization either, because three of our studied fern species with even longer leaf life spans (Lomariopsis recurvata, Mickelia bernoullii and Mickelia pergamentacea) were colonized by fewer foliicolous lichens (2-9 species after 26 months).…”
Section: Richness and Composition Of Three Groups Of Epiphylls On Fernsmentioning
confidence: 58%
“…The lichen symbiosis, a stable association of mainly fungal and photobiont partners as well as an associated microbiome, lends itself to the study of environmentally-driven gene content, because many species have remarkable environmental tolerances and maintain populations in different climate zones ( Kappen, 2000 ; Werth and Sork, 2014 ; Singh et al, 2017 ; Grimm et al, 2021 ; Jung et al, 2021 ; Tanunchai et al, 2022 ). Previous studies showed that environmental differentiation in lichens can be found at the level of single nucleotide polymorphisms (SNPs), which often significantly correlate with differences in geography and ecology and may thus be involved in environmental specialization ( Peksa and Skaloud, 2011 ; Castillo et al, 2012 ; Hodkinson et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The lichen symbiosis, a stable association of mainly fungal and photobiont partners as well as an associated microbiome, lends itself to the study of environmentally driven gene content, because many species have remarkable environmental tolerances and maintain populations in different climate zones (Grimm et al, 2021;Jung et al, 2021;Kappen, 2000;Medeiros et al, 2021;Sierra et al, 2020;Singh et al, 2017;Tanunchai et al, 2022;Werth & Sork, 2014). Population genomic analyses based on single nucleotide polymorphisms (SNPs) suggest the presence of genome-wide differentiation between populations in different climate zones (Dal Grande et al, 2017;Rolshausen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%